Analysis of neutron streaming through penetrations in the JET biological shielding - Stamatelatos, I. E.; Vasilopoulou, T.; Batistoni, P.; Conroy, S.; Obryk, B.; Popovichev, S.; Syme, D. B.; EFDA JET contributors, the (HNPS Advances in Nuclear Physics, 2019)
In the present work neutron streaming through large ducts and labyrinths of the Joint European Torus (JET) biological shielding was evaluated. Neutron fluence and ambient dose equivalent were calculated along the total length of the ducts. Monte Carlo calculations using the MCNP code were performed for both Deuterium-Deuterium (D-D) and Deuterium-Tritium (D-T) toroidal plasma discharge sources. The results of the calculations were compared against measurements performed using thermoluminescence detectors. This work contributes to the operational radiation protection effort to minimize collective radiation dose to personnel at JET and, moreover, provides important information from JET experience that may assist in the optimization and validation of the radiation shielding design methodology used in future fusion plants, such as ITER and DEMO.